A study on the pharmaceutical companies of DSE listed firms of Bangladesh for the period of 2018 to 2022 - Sushme, Sumaiya Selim (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.